Genetic Algorithm and Its Application in Scheduling System - Jian Ni; Ning-Ning Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
With the development of education and college expansion and consolidation in the Educational Management System Course Scheduling System has become more complex, and therefore necessary to design one for development, and reuse. Given this situation, this paper proposes a solution based on genetic algorithm. The results show that genetic algorithms can effectively solve the course timetabling problem. This method is easy to learn and apply, and do not rely on a special mode. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2365